Effect of supplementation of Zn-biocomplex in ration on the growth of young sheep - Supriyati .; B Haryanto (Jurnal Ilmu Ternak dan Veteriner, 2007)
The effect of supplementation of graded levels of Zn-bio-complex in concentrate on the growth of young sheep was studied. Fourty young Thin Tailled sheeps were devided into 4 groups of Zn-bio complex treatments. Zink-bio-complex was produced by IRIAP’s laboratory. King grass powder (CP = 10.4%) and concentrate (CP=15.5%) were given as a basal diet. King grass powder and drinking water were given ad libitum. The concentrate was given daily at 200 g h-1d-1 supplemented with 0 mg Zn kg-1 of DM (R1), 50 mg Zn kg-1 of DM (R2), 100 mg Zn kg-1 of DM (R3), and 200 mg Zn kg-1 of DM (R4). The initial live weight of sheep was 11.99 ± 0.17kg h-1. Live weight were measured fortnightly and feed consumption were measured daily. The experiment was carried out for 12 weeks with 4 weeks prior adaptation periods. Data obtained were analyzed statistically based on Completely Randomized Design. The results of experiment showed that the supplementation of Zn-bio-complex improved the live weight from 57.60 g h-1d-1 (R1) to 85.47, 72.14 and 67.86 g h-1d-1 with the feed conversion ratio improvement from 11.9 (R1) to 8.0, 9.6 and 10.5 for treatment R2, R3 and R4 respectively (P<0.05). The graded level of Zn-bio-complex did not affect daily feed intake which was 687, 686, 695 and 711 g h-1d-1 (P>0.05) for R1, R2, R3 and R4, respectively. It can be concluded that the supplementation of Zn-bio-complex at the level of 50 mg Zn kg-1 in daily concentrate resulted in the best response on live weight gain and feed conversion ratio of young sheep. Key Words: Zn-Biocomplex, Sheep, Liveweight Gain, Feed Conversion Ratio